BRAF inhibitors and their immunological effects in malignant melanoma. (3rd April 2022) - Adams, Rebecca; Coumbe, Jack E M; Coumbe, Ben G T; Thomas, Jennifer; Willsmore, Zena; Dimitrievska, Marija; Yasuzawa-Parker, Monica; Hoyle, Maximilian; Ingar, Suhaylah; Geh, Jenny L C; MacKenzie Ross, Alastair D; Healy, Ciaran; et al.
ABSTRACT: Introduction: The treatment of cutaneous melanoma has been revolutionized by the development of small-molecule inhibitors targeting the MAPK pathway, including inhibitors of BRAF (BRAFi) and MEK (MEKi), and immune checkpoint blockade antibodies, occurring in tandem. Despite these advances, the 5-year survival rate for patients with advanced melanoma remains only around 50%. Although not designed to alter immune responses within the tumor microenvironment (TME), MAPK pathway inhibitors (MAPKi) exert a range of effects on the host immune compartment that may offer opportunities for therapeutic interventions. Areas covered: We review the effects of MAPKi, especially BRAFi, on the TME, focusing on alterations in inflammatory cytokine secretion, recruitment of immune cells and their functions, both during response to BRAFi treatment and as resistance develops. We outline potential combinations of MAPKi with established and experimental treatments. Expert opinion: MAPKi in combination or in sequence with established treatments such as checkpoint inhibitors, anti-angiogenic agents, or new therapies such as adoptive cell therapies, may augment their immunological effects, reverse tumor-associated immune suppression, and offer the prospect of longer-lived clinical responses. Refining therapeutic tools at our disposal and embracing 'old friends' in the melanoma treatment arsenal, alongside new target identification, may improve the chances of therapeutic success.